Intratumoural CD8+ CXCR5+ follicular cytotoxic T cells have prognostic value and are associated with CD19+ CD38+ B cells and tertiary lymphoid structures in colorectal cancer - Fangze Wei; Xiaotian Xu; Jing Wang; Shi Wen Mei; Fu Qiang Zhao; Fei Huang; Ti Xian Xiao; Guo Jing Wang; Baojun Wei; Shengkai Huang; Wei Cui (Cancer Immunology, Immunotherapy)
Abstract Background Colorectal cancer (CRC) is the most common digestive cancer in the world. Microsatellite stability (MSS) and microsatellite instability (MSI-high) are important molecular subtypes of CRC closely related to tumor occurrence and progression and immunotherapy efficacy. The presence of CD8+ CXCR5+ follicular cytotoxic T (TFC) cells is strongly associated with autoimmune disease and CD8+ effector function. However, the roles of TFC cells in MSI-high CRC and MSS CRC are unclear. Here, we aimed to explore the characteristics of TFC cells in CRC and compare their biological functions between MSI-high and MSS CRC. Methods We explored the expression of TFC cell in tumor tissues and peripheral blood in our clinical cohort and public datasets. By combining single-cell RNA sequencing (scRNA-seq) and bulk RNA sequencing, we explored the potential function of TFC cells and developed a prediction model for CRC. We also compared the biological functions of these cells between MSS and MSI-high CRC and used flow cytometry and coculture experiments to explore their potential regulatory functions. Results TFC cell markers are downregulated in tumor tissues and patient peripheral blood vs. controls. The prediction model for CRC performed well in the training and validation cohorts (KM plot p < 0.001). MSS CRC patients exhibit enrichment of genes related to the cell cycle (MKI67) and T cell activation (CD38 and HLA-DR) and decreased enrichment of immune checkpoint markers (PD1, TIM3, and LAG3). The expression of TFC cell-related genes is positively correlated with that of CD8+IFN-γ+-related genes and closely related to that of TLS-related genes in MSS CRC. The proportion of TFC cells is positively correlated with that of CD19+CD38+ B cells in MSS CRC. Conclusions The prognostic prediction model has good predictive value. In MSS CRC, TFC cells function mostly in T cell activation and the cell cycle and have low expression of immune checkpoint molecules, which may influence the effectiveness of ICB therapy. TFC cells may regulate antitumor function by regulating CD19+ CD38+ B cells and TLSs.